1977
DOI: 10.2307/3280010
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Specificity of Antigen 5 of Echinococcus granulosus

Abstract: The presence of IgE antibodies to antigen 5 of Echinococcus granulosus was detected by means of radioimmunoelectrophoresis in the sera of two of six patients infected with E. multilocularis. Sera from three of these patients gave a precipitin band in gel diffusion tests identical to that produced by a monospecific rabbit anti-E. granulosus antigen 5 serum, when tested against whole hydatid fluid. Sera from 19 individuals infected with Fasciola hepatica, 20 with Schistosoma mansoni, and 5 with with Taenia sagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…However, the density of staining and its distribution in the membrane suggested that synthesis does occur here and that these membranes could be a source of antigen 5 found in hydatid cyst fluid. It was not surprising that antigen 5 was found in E. multilocularis because Yarzabal et al (1977a) have shown, using immunoelectrophoresis, that cross reactions occur between antigen 5 from E. granulosus cyst fluid and sera from patients infected with E. multilocularis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the density of staining and its distribution in the membrane suggested that synthesis does occur here and that these membranes could be a source of antigen 5 found in hydatid cyst fluid. It was not surprising that antigen 5 was found in E. multilocularis because Yarzabal et al (1977a) have shown, using immunoelectrophoresis, that cross reactions occur between antigen 5 from E. granulosus cyst fluid and sera from patients infected with E. multilocularis.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the antigens contained in hydatid cyst fluid have been purified and their chemical characteristics studied, namely the thermolabile lipoprotein antigen 5 (Capron et al, 1967;Bout et al, 1974) and the thermostable lipoprotein antigen B (Oriol et al, 1971;Oriol and Oriol, 1975). These antigens have been considered useful for the specific serological diagnosis of Echinococcus granulosus infection of man, especially antigen 5, although recent work has shown cross reactivity with Echinococcus multilocularis (Yarzabal et al, 1977a).…”
mentioning
confidence: 99%
“…Antigen B, a thermostable lipoprotein, presents in SDS-PAGE three subunits at 8/12, 16 and 20 kDa both in reducing and non reducing conditions. At present, the detection of antibodies to antigen 5 in sera of patients remains the most widely used diagnostic evidence for unilocular hydatid disease, although the presence of anti-antigen 5 antibodies have been reported in patients affected with other helminths (Varela-Diaz et al 1977, Yarzabal et al 1977. Recently the lowest subunit of antigen B at 8/12 kDa has been reported to be a putative diagnostic molecule using immunoblot/immunoprecipitation analysis (Shepherd & McManus 1987, Lightowlers et al 1989, Maddison et al 1989, Siracusano et al 1991, Leggat, Yang & McManus 1992, Kanwar et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…If CIEP is used as a screening test one observes that some sera positive to the CIEP test are negative to the IEP test (two cases) and vice versa (one case). In the latter case a positive result in the IEP test offers a high degree of certainty in the diagnosis of hydatid disease, since the detection of arc 5 of Capron et al (1967) has been shown to reflect an antigen moiety specific for Echinococcus infection in man (Varela-Diaz et al 1977, Yarzabal et al 1977. In the former cases, however, the diagnosis should be confirmed by complementary medical studies and follow-up because the CIEP test is not absolutely specific (Table 2), although the cross-reactivity observed is minimum.…”
Section: Discussionmentioning
confidence: 99%